Principles and practice of chiropractic (McGraw-Hill, 2005)
Principles and Practice of Chiropractic is the most complete and authoritative textbook of chiropractic available. It provides a comprehensive overview of the entire field of chiropractic, including its history and philosophy, social implications, basic sciences, examination techniques, treatment methods, and management of specific disorders.